Perceptions Of Covid 19 Survivors: Prevention and Transmission Education Virus in Era New Normal - Qori Hajidah Arianti; Ifa Elok Magfiroh Oktaviani; Ria Safitri; Mochammad Ilyas Junjunan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of coronavirus that causes disorders of the respiratory system, acute pneumonia, and can lead to death. This community service is intended to provide understanding and knowledge about the prevention and transmission of COVID-19 to the wider community. This health education webinar community service activity is carried out online via Zoom. The material presented was about preventing and transmitting the virus during a pandemic according to the perception of COVID-19 survivors. Prior to the implementation of the educational webinar, participants were asked to register as well as fill out a questionnaire to measure the level of knowledge about preventing the transmission of COVID-19 (pre-test). Then at the end of the meeting, participants were asked to fill out the attendance list, and then fill out the questionnaire again (post-test). The results of the educational activity questionnaire showed that there was a good change in the level of knowledge between before and after being given educational materials with an average pre-test score of 63.84 and a post-test of 91.53 from 13 participants. So it can be concluded that this education can confirm audiovisually which can change the level of knowledge for the better.